Vitamin D in Follicular Fluid Correlates With the Euploid Status of Blastocysts in a Vitamin D Deficient Population - Arnanz, Ana; De Munck, Neelke; El Khatib, Ibrahim; Bayram, Aşina; Abdala, Andrea; Melado, Laura; Lawrenz, Barbara; Coughlan, Carol; Pacheco, Alberto; Garcia-Velasco, Juan A.; Fatemi, Human M. (Frontiers in Endocrinology, 2021)
Context: The widespread distribution of the Vitamin D (VitD) receptor in reproductive tissues suggests an important role for VitD in human reproduction. The assessment of patient´s VitD is based on the 25-hydroxyvitamin D (25(OH)D) metabolite measurement. However, most of the circulating 25(OH)D is bound to either VitD-binding protein (VDBP) (88%) or albumin (12%) and less than 1% circulates free. Objective: To determine a possible correlation between VitD levels in serum (S) and follicular fluid (FF) and blastocyst ploidy status in patients undergoing infertility treatment. Methods: A prospective observational study was performed including couples planned for preimplantation genetic testing for aneuploidies (PGT-A) from ART Fertility Clinics. Patients were classified according to their 25(OH)D-Serum levels: VitD deficient group <20ng/ml and insufficient/replete 20ng/ml defined as VitD non-deficient group. Results: Serum samples and 226 FF from individual follicles were collected for 25(OH)D, bioavailable 25(OH)D, free 25(OH)D and % free 25(OH)D measurement. 25(OH)D-S in VitD deficient and non-deficient were 13.24.0ng/ml vs 32.39.2ng/ml; p<0.001. FF from 40 and 74 biopsied blastocysts was analysed of which 52.5% and 60.8% were euploid (p=0.428), respectively. In VitD deficient patients , mean 25(OH)D-FF, bioavailable 25(OH)D-FF and free 25(OH)D-FF were higher in euploid vs aneuploid blastocysts (18.36.3ng/ml vs 13.94.8ng/ml; p=0.040; 1.50.5ng/ml vs 1.10.4ng/ml; p=0.015; 0.0050.002ng/ml vs 0.0030.001ng/ml; p=0.023, respectively), whilst no differences were found in VitD non-deficient patients (37.912.3ng/ml vs 40.613.7ng/ml; p=0.380; 3.11.1ng/ml vs 3.31.2ng/ml; p=0.323; 0.010.003ng/ml vs 0.01 0.004ng/ml; p=0.319, respectively). Conclusion: VitD non-deficient patients have a significantly higher probability of obtaining a euploid blastocyst compared to VitD deficient patients (OR:33.36, p=0.002).